Symbiosis of a P2‐family phage and deep‐sea Shewanella putrefaciens. (30th August 2019) - Liu, Xiaoxiao; Tang, Kaihao; Zhang, Dali; Li, Yangmei; Liu, Zhe; Yao, Jianyun; Wood, Thomas K.; Wang, Xiaoxue
Summary: Almost all bacterial genomes harbour prophages, yet it remains unknown why prophages integrate into tRNA‐related genes. Approximately 1/3 of Shewanella isolates harbour a prophage at the tmRNA ( ssrA ) gene. Here, we discovered a P2‐family prophage integrated at the 3′‐end of ssrA in the deep‐sea bacterium S . putrefaciens . We found that ~0.1% of host cells are lysed to release P2 constitutively during host growth. P2 phage production is induced by a prophage‐encoded Rep protein and its excision is induced by the Cox protein. We also found that P2 genome excision leads to the disruption of wobble base pairing of SsrA due to site‐specific recombination, thus disrupting the trans‐translation function of SsrA. We further demonstrated that P2 excision greatly hinders growth in seawater medium and inhibits biofilm formation. Complementation with a functional SsrA in the P2‐excised strain completely restores the growth defects in seawater medium and partially restores biofilm formation. Additionally, we found that products of the P2 genes also increase biofilm formation. Taken together, this study illustrates a symbiotic relationship between P2 and its marine host, thus providing multiple benefits for both sides when a phage is integrated but suffers from reduced fitness when the prophage is excised.